IL-4 Level in Rifampicin-Sensitive and Rifampicin-Resistant Lung Tuberculosis Patients - Joko Susanto; Jusak Nugraha; Soedarsono Soedarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Tuberculosis remains a global health burden. Mycobacterium tuberculosis infection causes humoral and cellularresponses. Macrophages of patients with pulmonary tuberculosis evolve M1 polarization that blocks infection orimmunosuppressive M2, promoting tissue repair mediated by IL-4, IL-10, and IL-13. Previous research showed a decrease ofIL-4R and IL-10 expression in lung macrophages of anti-TB drug resistance. A molecular test can detectrifampicin- resistance. There has been no study, which showed the difference in serum IL-4 levels in rifampicin-sensitive andrifampicin-resistant tuberculosis patients. This study aimed to determine the difference between circulating IL-4 levels inrifampicin-sensitive and rifampicin-resistant pulmonary tuberculosis patients. This cross-sectional observational studyconsecutively recruited subjects based on positive molecular and acid-fast bacilli microscopic examination from MDR-TBClinic of the Dr. Soetomo Hospital between December 2018 to March 2019. Subjects were classified into arifampicin-sensitive and rifampicin-resistant group. On ELISA measurement, IL-4 data were analyzed with SPSS version 17.Mann-Whitney U test and ROC analysis tests were performed, and p < 0.05 was significant for α=0.05 (95% CI). There wassignificant difference between rifampicin-sensitive group (420±281 pg/mL) and rifampicin-resistant group(253±279 pg/mL) (p=0.014). Receiver operating characteristics analysis showed AUC 0.70, the sensitivity of 81.5%, thespecificity of 63.6%, and the cut-off value of 235.6 pg/mL. There was a significantly higher level of circulating IL-4 in therifampicin-sensitive group than the rifampicin-resistant group. IL-4 level in healthy subjects should be measured as thenormal value in the population. Immunology and metabolic parameters should be performed to increase samplehomogeneity. Further study was also needed to understand the IL-4 role in rifampicin resistance of lung tuberculosispatients in the Indonesia population.